1993
DOI: 10.1007/bf01321226
|View full text |Cite
|
Sign up to set email alerts
|

Family preservation using multisystemic treatment: Long-term follow-up to a clinical trial with serious juvenile offenders

Abstract: In a randomized clinical trial, multisystemic family preservation was shown to

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
121
2
4

Year Published

1996
1996
2013
2013

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 286 publications
(128 citation statements)
references
References 18 publications
1
121
2
4
Order By: Relevance
“…Importantly, central aspects of MST are consistent with the recent public health agenda concerning violence prevention. Moreover, as demonstrated from the findings of controlled clinical trials (Henggeler et al, 1992(Henggeler et al, , 1993Borduin et al, 1995), the success of MST supports the viability of the public health approach when applied to serious juvenile offenders.…”
Section: Introductionmentioning
confidence: 83%
See 2 more Smart Citations
“…Importantly, central aspects of MST are consistent with the recent public health agenda concerning violence prevention. Moreover, as demonstrated from the findings of controlled clinical trials (Henggeler et al, 1992(Henggeler et al, , 1993Borduin et al, 1995), the success of MST supports the viability of the public health approach when applied to serious juvenile offenders.…”
Section: Introductionmentioning
confidence: 83%
“…The survival analysis shown in Figure 1 reveals that at 2·4 years follow-up, MST approximately doubled the survival rate (i.e. the percentage of youth not rearrested) of these serious juvenile offenders (Henggeler et al, 1993). Moreover, the relative efficacy of MST was neither moderated by demographic characteristics (i.e.…”
Section: Two Recent Controlled Clinical Trials Of Mstmentioning
confidence: 97%
See 1 more Smart Citation
“…Scott Henggeler and Charles Borduin in university-based quasi-experimental and randomized controlled trials (RCTs) in which doctoral students served as MST therapists for inner-city and chronic juvenile offenders (see, e.g., Borduin et al, 1995;Henggeler et al, 1986) with continued development and validation of MST in RCTs involving community-based mental health practitioners employed either by the university investigators or community mental health centers (see, e.g., Henggeler, Melton, Brondino, Scherer, & Hanley, 1997;Henggeler, Melton, & Smith, 1992;Henggeler, Melton, Smith, Schoenwald, & Hanley, 1993;Henggeler, Pickrel, & Brondino, 1999). Across numerous RCTs, MST consistently achieved significant reductions in rates of recidivism and conduct problems for criminal offending and substance abuse, with follow-ups ranging from 1.7 to 13.7 years (for review, see Henggeler & Sheidow, in press (Elliott, 1998) have identified MST as an effective treatment for serious antisocial behavior in adolescents.…”
Section: Mst Research Outcomesmentioning
confidence: 99%
“…Uno de los estudios que ha mostrado mayor benefi cio en relación con el costo es la llamada terapia multisis témica de Henggeler, 49 que se basa en la premisa según la cual la familia es parte de una red interconectada en la que padres e hijos interactúan con factores externos como la escuela y el ambiente laboral. Por lo tanto, las intervenciones dirigidas sólo a los padres pueden no ser eficaces si no hay cambios en el contexto en que éstos se desenvuelven.…”
Section: Prevención Terciariaunclassified